Influence of ambipolar and Hall effects on vorticity in three-dimensional simulations of magneto-convection. (8th February 2021) - Khomenko, E.; Collados, M.; Vitas, N.; González-Morales, P. A.
Abstract : This paper presents the results of the analysis of three-dimensional simulations of solar magneto-convection that include the joint action of the ambipolar diffusion and the Hall effect. Three simulation runs are compared: one including both ambipolar diffusion and the Hall effect; one including only ambipolar diffusion and one without any of these two effects. The magnetic field is amplified from initial field to saturation level by the action of turbulent local dynamo. In each of these cases, we study 2 h of simulated solar time after the local dynamo reaches the saturation regime. We analyse the power spectra of vorticity, of magnetic field fluctuations and of the different components of the magnetic Poynting flux responsible for the transport of vertical or horizontal perturbations. Our preliminary results show that the ambipolar diffusion produces a strong reduction of vorticity in the upper chromospheric layers and that it dissipates the vortical perturbations converting them into thermal energy. The Hall effect acts in the opposite way, strongly enhancing the vorticity. When the Hall effect is included, the magnetic field in the simulations becomes, on average, more vertical and long-lived flux tube-like structures are produced. We trace a single magnetic structure to study its evolution pattern and the magnetic field intensification, and their possible relation to the Hall effect. This article is part of the Theo Murphy meeting issue 'High-resolution wave dynamics in the lower solar atmosphere'.